2010
DOI: 10.1108/02610151011042439
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating our diversity: creating an inclusive climate in a US university

Abstract: PurposeThe purpose of this paper is to provide insight and reflections on the experience of initiating a diversity effort from the perspective of members of a university change team. The process, challenges, and recommendations for institutions that may embark on a formal initiative towards becoming a more inclusive and equitable community are discussed.Design/methodology/approachThe multicultural organizational development (MCOD) model is operationalized at this university. MCOD is a long‐term, complex, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Paradoxical and fragmented processes towards gender equality take place, and this promotion-oriented management of gender equality even has the potential to divert attention from gender and other forms of inequality (e.g. migration background, age, disability, class) in the evaluation of procedures and the management of individuals (Newman and Ashworth, 2003;Gavino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxical and fragmented processes towards gender equality take place, and this promotion-oriented management of gender equality even has the potential to divert attention from gender and other forms of inequality (e.g. migration background, age, disability, class) in the evaluation of procedures and the management of individuals (Newman and Ashworth, 2003;Gavino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been paid to enrich the conceptualization of inclusion to tackle the polarization of inclusion versus exclusion, emphasizing the influence of power, politics and historical effects on inclusion. Via a case study, Gavino et al (2010) demonstrated a long-term, complex organizational change process in a university effort to build an inclusive climate. Later efforts have been influenced by critical perspectives (Adamson et al , 2021) and produced several concepts capturing the processual and relativistic nature of inclusion, such as partial inclusion (Dawson, 2006), hybrid inclusion (Dobusch, 2014), peripheral inclusion (Rennstam and Sullivan, 2018) and privation of inclusion (Asey, 2022), suggesting there is a range or levels of inclusion, and that individuals can feel both included and excluded, simultaneously.…”
Section: Inclusion Conceptualizationsmentioning
confidence: 99%
“…The impetus for this interview was initiated by a conversation with my dear friend Dr Bailey Jackson. In a recent visit, we reflected on the work with the MCOD model that brought us together many years ago (Gavino et al, 2010) and the ongoing lack of traction on faculty diversity initiatives. Dr Jackson pointed out that implementing interventions at various levels of the institution may appear as plausible solutions to dilemmas such as faculty diversity, but are ineffective and do not sustain the changes necessaryas it is at the institutional or system level that change needs to occur.…”
Section: Interview With Dr Bailey Jacksonmentioning
confidence: 99%